2000
DOI: 10.1111/j.1939-1676.2000.tb01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Idiopathic Inflammatory Bowel Diseases of the Horse

Abstract: A review of reported cases of inflammatory bowel diseases (IBDs) of horses for which no etiology was identified included cases of granulomatous enteritis (GE), multisystemic eosinophilic epitheliotropic disease (MEED), lymphocytic-plasmacytic enterocolitis (LPE), and idiopathic eosinophilic enterocolitis (EC). The terms EC and MEED were both used to describe a disease in horses characterized by infiltration of intestine and extraintestinal tissues with eosinophils. We use EC to describe IBD characterized by on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
185
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(187 citation statements)
references
References 47 publications
0
185
1
1
Order By: Relevance
“…[3][4][5][6][7] Eosinophilic infiltrates of equine lungs are observed during parasitic infections or allergic condition 8,9 but eosinophilic pneumonia with vasculitis, which are not associated with parasitic infection and without the evidence of involvement of other organs have not been previously reported in horses. In the present study, we describe the gross and microscopic lesions of idiopathic eosinophilic pneumonia with associated vasculitis in 11 horses.…”
mentioning
confidence: 98%
“…[3][4][5][6][7] Eosinophilic infiltrates of equine lungs are observed during parasitic infections or allergic condition 8,9 but eosinophilic pneumonia with vasculitis, which are not associated with parasitic infection and without the evidence of involvement of other organs have not been previously reported in horses. In the present study, we describe the gross and microscopic lesions of idiopathic eosinophilic pneumonia with associated vasculitis in 11 horses.…”
mentioning
confidence: 98%
“…This finding was mirrored by a review of the evidence by Schumacher and others (2000), which found that the diagnosis was supported by rectal biopsy in approximately 50 per cent of cases of granulomatous enteritis and MEED. However, a diagnosis of lymphocytic-plasmacytic enteritis or eosinophilic enterocolitis was unlikely to be supported by rectal biopsy (Lindberg and others 1996, Schumacher and others 2000). A rectal biopsy is a useful procedure, but relies on the rectal mucosa having a similar cell infiltration and pathology as the grossly affected intestine, which will only occur in a proportion of cases.…”
Section: Diagnostic Testsmentioning
confidence: 84%
“…The key to differentiating this condition from the other causes of IBD is that this disease is multisystemic, so most cases will also present with clinical signs related to other body systems. In previous reports, all horses with MEED have presented with weight loss, approximately 63 per cent had diarrhoea, 63 per cent had dermatological changes and just 4 per cent presented with colic (Schumacher and others 2000). Other clinical signs may include ulceration of the tongue and mouth, nasal discharge due to respiratory involvement, evidence of pancreatitis or lymphadenopathy (Fig 8).…”
Section: Types Of Ibdmentioning
confidence: 95%
“…Occasionally it is seen in cattle and cats (Griffin and Meunier 1990, Ramirez and others 2012). It can present with various clinical symptoms, varying from acute colic to weight loss and depression in horses to chronic diarrhoea and weight loss in dairy cows (Pass and Bolton 1982, Cebra and others 1998, Schumacher and others 2000). Dogs and cats often present with vomiting, diarrhoea and weight loss (Griffin and Meunier 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the diagnosis is made on the basis of exclusion and trialled treatment with anthelmintics, dietary changes and antibiotics (Nelson and Couto 2009, Smith 2009). In other cases, intestinal biopsies are taken, either in vivo or at postmortem (Schumacher and others 2000, Kleinschmidt and others 2006). In horses, histology of these cases normally shows extensive infiltration of the lamina propria and submucosa with eosinophils, mast cells, macrophages and lymphocytes (Pass and Bolton 1982).…”
Section: Discussionmentioning
confidence: 99%